Os deficientes visuais e o acesso à informação na seção Braille da Biblioteca Pública Arthur Vianna e Biblioteca Central da Universidade Federal do Pará: um estudo de usuários - DIREITO, Eduardo Ramos (2017)
Presents an analysis of how visually impaired students are assisted in the Braille sector of the Arthur Vianna Public Library and the UFPA Central Library, in order to identify and present their information needs. The methodology used was the qualitative research technique collected through interviews through semi-structured interviews with semi-open questions, and documentary analysis was also used. Data collection was carried out with a universe of 10 users and 7 employees from both libraries, from March 20 to 22, 2017. After data collection and analysis, it was concluded that users access all types of information On the computer, but mainly seek academic information, news and entertainment, having their information needs mostly satisfied. In relation to the difficulty of access to information, the lack of accessibility of the sites was the most cited. Through the lines of the users can observe the impact that information technology has had on their lives.